SEISMIC SAFETY OF THE PRECAST BALCONY CANTILEVER ELEMENTS FOR PREVENTION OF THERMAL BRIDGES - Boris Azinović; David Koren; Vojko Kilar (AR: Arhitektura, Raziskave, 2014)
In the paper the seismic response of precast balcony cantilever structural elements for prevention of thermal bridges was analysed. This solution has been developed in seismic non-prone areas with the main purpose of eliminating a thermal bridge at the point where the balcony is fixed to the building. The solution has been specially made to withstand vertical static loading, not accounting for eventual vertical seismic loads in the case of transferring the solution to more active seismic zones. This paper deals with the seismic analysis of existent precast cantilever elements exposed to vertical accelerations and has proven that some elements in the case of lifting are not sufficient from the safety point of view. The results of the main research results obtained by numerous seismic analyses can be summarized as follows: 1) the insertion of a precast load-bearing thermal insulation element increases the flexibility of RC fixed base cantilevers and therefore limits their length to 300–400 cm, 2) vertical seismic loads can result in the cantilever uplift, which means that tensile stresses could appear also at the bottom of the cross-section 3) precast elements, that appear on the Slovenian market to this day, do not have the appropriate steel reinforcement in the bottom part of the cross-section. For this reason, the possibility of damage is considerably higher for precast cantilever structural elements than for RC fixed base cantilevers. Statistically calculated probability of cantilever uplift for Ljubljana, which would result in severe damage, is relatively low (3% in the 50-year life span). However, the calculated value is greater than the maximum acceptable level of seismic risk for collapse. One of the possible solutions to prevent the negative influences of cantilever uplift is to consider the proper reinforcement also at the bottom of the precast elements' crosssection, or by other measures preventing uplift.